Study of the psychological preparation on the dental care of children with special needs - Rocha, João Carlos (Brazilian Dental Science, 2013)
The psychology in Dentistry is a great challenge for the clinicians during the care of their patients. The conditioning of a patient to achieve a behavior meeting the professional’s needs for developing a procedure within the quality standards is necessary. When this conditioning focuses on the child patients the challenge is even greater because the child will use all ways to make difficult the action of the clinician due to fear or discomfort. The ability of the dentist to condition the patient will be directly proportional to the training and theoretical knowledge acquired. Considering the Patients with Special Needs (PSN), this training should be differentiated because there is the physical, cognitive, and the previous dental/medical history in addition to the psychological and emotional difficulties. The aim of this study was to evaluate the profile of the patient to be conditioned satisfactorily and which conditioning techniques would be more efficient to ambulatory dental care of PSN. Thirty patients, both genders, aged from 20 months to 11 years-old who were enrolled at the ambulatory treatment of NEAPE were observed. It was concluded that when there is the cognitive development of the individual, they are able to be conditioned for the ambulatory care; the use of auxiliary methods is important in the conditioning for the ambulatory care of the individuals; the syndromic patients had the best results for the conditioning aiming to the ambulatory care; there was a significant improvement in the behavior of individuals between the first and last appointments.